Urban Plans of Ekaterinoslav Viceroyalty: Hierarchical Structure and Spatial Borders - Olga Vladimirovna Baeva; Armen Yurievich Kazaryan (Известия Уральского федерального университета. Серия 2: Гуманитарные науки)
The second half of the eighteenth and early nineteenth centuries marked a period of significant urban restructuring, with the establishment of numerous new cities and the redesign of existing ones. These urban developments were meticulously planned according to the principles and ideals of Neo-classical architecture, a style that dominated the architectural landscape during this era. A considerable number of these cities were established in the underdeveloped and sparsely populated southern regions of Russia. This geographical context presented distinctive prospects for the implementation of an innovative urban planning policy. This policy was characterised by the creation of a geometrically precise urban layout, aimed at enhancing the quality of life and disseminating imperial cultural and political values. The focus of this study is on the cities of the Ekaterinoslav Vicegerency and Ekaterinoslav Province, which were founded in the 1770s–1780s, when the first plans for them were created. Confirmation of the plans did not take place until the 1810s and 1820s. The review study of the principles of the formation of the hierarchical structure and boundaries of the cities of the territory is based on the analysis of long-term plans from different years found by the authors of the article in archives, as well as published ones. The new cities of the region were devoid of a significant medieval architectural heritage. Consequently, when devising plans, architects and surveyors were granted greater autonomy in selecting compositional techniques and implementing the planning principles of Neo-classicism. The article analyses the characteristics of urban development in the territory of the Ekaterinoslav Vicegerency, with a focus on the identification of the features of the hierarchical structure and the spatial boundaries of the cities. The authors demonstrate a correlation between the urban layout and its administrative status, which is discernible within the framework of long-term urban planning. They also analyse the role of functionally different squares, the differences between central and peripheral buildings, the nature of the main streets in the orthogonal layout system and their connections with intercity roads. A particular emphasis is placed on the attitude toward the river in the urban layout, its role as an internal artery, and, in a manner more typical of the cities of the vicegerency, its function as a natural boundary of the city. Rectilinear ramparts, ditches, and other restrictive lines on city plans served to delineate the limits of urban space development. Assuming that this is the case, it can be posited that these elements are a manifestation of the principle of “timelessness” of the layout of Russian cities, as discussed in scholarly literature.